Low Power Emission Pulse Generation Circuit Based on n-Type Amorphous In-Ga-Zn-Oxide Transistors for Active-Matrix Organic Light-Emitting Diode Displays - Min-Kyu Chang; Ji Hoon Kim; Hyoungsik Nam (Micromachines)
This paper presents a low power emission (EM) pulse generation circuit using n-type amorphous In-Ga-Zn-Oxide (a-IGZO) semiconductor thin-film transistors (TFTs). The low power consumption is achieved by avoiding the shoot-through current paths through an optimized inverter circuit. The proposed circuit consists of 12 TFTs and 2 capacitors including 6 TFTs and 1 capacitor for the inverter circuit to control the pulling-down TFTs. In addition, the wider variance range of the threshold voltage (<semantics>Vth</semantics>) from <semantics>−4</semantics> V to <semantics>2.5</semantics> V is covered by additional 6 TFTs for series-connected two transistor (STT) schemes and two low supply voltages to take into account the negative <semantics>Vth</semantics> of depletion-mode TFTs. The simulation of 30 EM circuits is conducted over a 6.1-inch active-matrix organic light-emitting diode display of 120 Hz refresh rate and 3840 × 2160 (UHD) resolution. The power consumption of the EM circuit with the proposed inverter is measured at the low values from 0.836 mW to 0.568 mW over pulse widths from 3 to 2157 horizontal times. It is ensured that the proposed circuit achieves the low power consumption regardless of pulse widths.